Pesan dalam Berkomunikasi - Efendi, Erwan; Fauzan, Ridho; Makwa, Jannatun; Agustin, Imel; Mustofa, Wildan; Aqil , Muhammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This journal aims to investigate the concept of messages in communication, analyze the message communication process, and identify its influence on human understanding and interaction. By understanding the role of messages in communication, we can become more effective communicators and be able to better manage messages in various contexts. The method used in this research uses the Systematic Literature Review (SLR) to find out the most appropriate method. This research applies three stages, namely: planning, implementation. In the communication process, messages have a key role in transmitting information, building relationships, influencing behavior, and increasing understanding. The importance of good understanding of messages in the context of communication is very relevant in various aspects of human life